ARE FUTURE EFL TEACHERS READY FOR INCLUSION? A CONVERGENT MIXED METHOD STUDY OF SELF-EFFICACY AND ATTITUDES - Binti Muifatun Nazilah; Farah Mulyawati; Suharyadi; Nur Mukminatien; Niamika El Khoiri (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2025)
Inclusive education is gaining prominence in English language teaching, especially in preparing future teachers to address diverse learner needs. Understanding self-efficacy and attitudes is essential, as both shape how teachers perceive their roles and determine their willingness to implement inclusive practices. This study examines the self-efficacy and attitudes of 68 Indonesian EFL pre-service teachers who were selected through purposive sampling from those enrolled in an Inclusive Education in ELT course. Using a convergent mixed methods design, data were collected through an adopted questionnaire and semi-structured interviews. Three participants were further selected for interviews using convenience sampling to provide deeper qualitative insights. Quantitative findings indicated that participants demonstrated a moderate level of self-efficacy and a moderately positive attitude toward inclusive teaching. A positive correlation was found between self-efficacy and attitudes, with self-efficacy in using inclusive instruction emerging as the only significant predictor of attitudes. Qualitative data supported and enriched these findings by revealing participants’ reflections on both the value and concerns in implementing inclusive practices. Overall, the study underscores the importance of targeted professional development in preparing EFL pre-service teachers for inclusive classrooms.